ANALISIS PELAKSANAAN PENDIDIKAN KARAKTER DI SMA NEGERI 3 SEMARANG (Studi Pada Kelompok Mata Pelajaran IPS) - Surasmini, S.; Joebagio, Hermanu; Wasino, W. (Sebelas Maret University (UNS), 2017)
The purpose of this research is to know the ability of teachers in identifying, integrating and evaluating the implementation of character education in teaching and learning activities. This research uses a single case, so that the relevant research strategy is a case study. Data gathering techniques using the technique of nontes (now, observation, interviews, and documents). To check the validity of the data used triangulation of methods and sources. The results obtained from this research, the cultivation of the values of character education in social science subjects which is conducted by the teacher to the learner is found almost balanced between frequent and sometimes embed. This is shown by the percentage of students who said that teachers often impart the character values in the form of granting or giving examples of the Queen to learners as much as 43%, sometimes there are also teachers who instilled the values of character with insert to content learning is evidenced by the 45% of students says sometimes teachers inculcate character to students, 10% of the students said the teacher always instill the value of character, 2% of students said the teacher never imparts character values. Based on the results obtained in this study, it can be concluded that the cultivation of the values character education can be integrated through the study of subjects social science in particular history in Senior High School 3 Semarang